7-Eleven Melejit Lewat Lifestyle - Freddy P. Simbolon (Binus Business Review, 2012)
The landscape of convenient store businesses or minimarkets now have changed. Location base strategy has not been sufficient any longer now. Psychographic and Demographic approaches tend to share a newly built power. Two main variables that have been managed concern at retail level are the store image and the store atmosphere. While the store image dimensions that can be put into considerations are the items offered, services committed, who and the amount of customers, physical facilities, promotion and convenience, store atmosphere, especially the involvement of affections through built emotions status in store which possibly uncautioned wholly by the customers when doing shopping. Since officially opened, the 7-Eleven had offered unique facilities. Instead of providing instant foods and beverages for 24 hours, the 7-Eleven also provides convenient corners and tables to eat and drink and provides chatting facilities for customers who need it. These make other modern retailers following the concept: opened for 24 hours and providing chatting facilities for young people.